Development of Desmos Electronic Students’ Activities Sheet (E-LKPD) based on the Problem Based Learning to Improve Students’ Mathematical Critical Thinking Skills - Ani Minarni; Leny Nauliana Barus (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to improve students' mathematical critical thinking skills using the developed Desmos Electronic Student Worksheet (E-LKPD) based on Problem Based Learning, student responses after using the Desmos E-LKPD, and the practicality of Desmos-based E-LKPD Problem-Based Learning was developed. From the research results it is known that: (1) Based on the aspect of critical thinking skills, the aspect of interpretation increases by 9%, the aspect of analysis increases by 18%, the aspect of evaluation increases by 42%, and the aspect of inference increases by 48%. (2) The results of the students' answers are included in the good category with a proportion of 80.31%. (3) The Problem Based Learning-based E-LKPD Desmos that has been developed has met the effective criteria in terms of the assessment of media experts, material experts, and user experts in the valid category, classical learning completeness has reached 80.65%, and Gain results of 0 .5 with medium category. The practicality test results get 92.18% in the very practical category.